2007
DOI: 10.1161/01.hyp.0000258215.26755.20
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure and Cardiovascular Outcome in Relation to Perceived Sleep Deprivation

Abstract: Abstract-Sleep deprivation induced by cuff inflations during overnight blood pressure (BP) monitoring might interfere with the prognostic significance of nighttime BP. In 2934 initially untreated hypertensive subjects, we assessed the perceived quantity of sleep during overnight BP monitoring. Overall, 58.7%, 27.7%, 9.7%, and 4.0% of subjects reported a sleep duration perceived as usual (group A), Ͻ2 hours less than usual (group B), 2 to 4 hours less than usual (group C), and Ͼ4 hours less than usual (group D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 34 publications
(35 reference statements)
0
79
0
4
Order By: Relevance
“…13,14 As sleep deprivation resulting from the repeated cuff-inflame during overnight BP monitoring leads to BP elevation, the clinical implications of high nocturnal BP levels obtained in such cases should be interpreted with caution. In fact, Verdecchia et al 15 suggested that the nocturnal BP of patients who perceived sleep deprivation of at least 2 h of lost sleep lost its prognostic significance with at least 7 years of follow-up for mortality and also in terms of composite cardiovascular risk. Moreover, Hensken et al 16 also reported that the association between nocturnal BP levels and cardiac hypertrophy tended to be weaker when sleep was subjectively disturbed during overnight BP monitoring.…”
Section: How To Evaluate Nocturnal Bpmentioning
confidence: 99%
“…13,14 As sleep deprivation resulting from the repeated cuff-inflame during overnight BP monitoring leads to BP elevation, the clinical implications of high nocturnal BP levels obtained in such cases should be interpreted with caution. In fact, Verdecchia et al 15 suggested that the nocturnal BP of patients who perceived sleep deprivation of at least 2 h of lost sleep lost its prognostic significance with at least 7 years of follow-up for mortality and also in terms of composite cardiovascular risk. Moreover, Hensken et al 16 also reported that the association between nocturnal BP levels and cardiac hypertrophy tended to be weaker when sleep was subjectively disturbed during overnight BP monitoring.…”
Section: How To Evaluate Nocturnal Bpmentioning
confidence: 99%
“…If sleep is perceived as "poor" during overnight BP monitoring (duration of sleep Ͻ2 hours less than usual), nighttime BP rises, and its prognostic significance appears to be no longer reliable. 52 An objective consideration is that 24-hour ABP monitoring is the only reasonable and established way to measure nighttime BP and the day-night BP changes. Indeed, some modern instruments for home BP measurements could be set to take some occasional BP measurements even during the night, 53 but their clinical use to refine organ damage prediction and risk stratification should be further investigated.…”
Section: Bp Changes From Day To Nightmentioning
confidence: 99%
“…There may be 2 types of non-dippers (with and without other risk factors such as SAS and/or diabetes), and the risks of non-dipper status may be partly explained by the subjects' backgrounds that lead to non-dipper status. Verdecchia, et al [23] reported that non-dippers with sleep deprivation induced by cuff inflations during nighttime ABPM did not have increased cardiovascular mortality. Some of the mechanisms by which SAS may increase blood pressure include the reninangiotensin-aldosterone system [24,25], sympathetic nerve activation [26], endothelial dysfunction [27], endothelin [28], and oxidative stress [29].…”
Section: Discussionmentioning
confidence: 99%